2016
DOI: 10.1186/s40824-016-0069-z
|View full text |Cite|
|
Sign up to set email alerts
|

Superior absorption and retention properties of foam-film silver dressing versus other commercially available silver dressing

Abstract: BackgroundThe aim of this study is to investigate the physicochemical and structural properties of Medifoam®Silver and to compare with other commercially available silver-containing polyurethane (PU) foam dressing in vitro.MethodsSurface and cross-section of four polyurethane foam dressings were assessed with field-emission scanning electron microscope. Thickness, density, tensile strength, elongation, absorption rate, absorption/retention capacity and water-vapor transmission (WVT) were measured to compare ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(30 reference statements)
0
9
0
2
Order By: Relevance
“…However, some researchers assumed the evidence for silver-based dressings in the prevention of infections to be insufficient and the costs too high [ 31 , 32 ]. Foam-based dressing is generally recommended for exudate wounds due to its absorbent property and is not recommended for use in dry wounds [ 28 , 33 ]. According to the results of our study and those reported in the literature, wound characteristics should be taken into consideration when choosing the covering material in driveline care protocol.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers assumed the evidence for silver-based dressings in the prevention of infections to be insufficient and the costs too high [ 31 , 32 ]. Foam-based dressing is generally recommended for exudate wounds due to its absorbent property and is not recommended for use in dry wounds [ 28 , 33 ]. According to the results of our study and those reported in the literature, wound characteristics should be taken into consideration when choosing the covering material in driveline care protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The original article contains an error [1] in the Discussion section, in the following sentence:“[…] highly absorptive and moisture retentive dressings such as BETAplast, are a welcomed addition to wound management armamentarium.” …”
Section: Erratummentioning
confidence: 99%
“…Silver ions can be released from the polymer matrix into the wound fluid or exudate and act against a wide spectrum of pathogens such as gram-negative and gram-positive bacteria, yeast and viruses. Because of this, silver-containing foam dressings have been commonly used for healing wounds, including burns, diabetic ulcers, and surgical wounds [21,22]. Silver-based biocides are nevertheless relatively expensive and in the case of nanoparticles it is necessary to implement complicated processes to disperse them homogeneously in the polymer matrix [19].…”
Section: Introductionmentioning
confidence: 99%